Motivations for Socially Responsible Investing: The Impact of Attitudes, Subjective Norms, and Financial expectations - Zhang, Xiaojia (International Journal of Global Economics and Management, 2024)
This study looks forward to exploring and understanding what the reasons for the desire of retail investors in might be making Socially Responsible Investments (SRI) in the Chinese stock market and to get an estimate of how valid the theory of reasoned action (TRA) could be. This is intended to look at how such factors as attitude, subjective norms, financial expectations, and risk propensity influence investors to engage in SRI in China. This research builds on previous studies that introduced financial expectations as a crucial new construct, enhancing the depth and rigor of TRA model in examining investment intentions. This assumption posits that investors comprehensively consider the investment situation, weighing not only its societal impact but also its financial returns, and only after considering these outcomes comprehensively will they make decisions on SRI. Risk propensity has been used as moderator in this research model relationship. Whether risk propensity influences the association between attitude, subjective norms, and financial expectations with investment intentions has been test in this study. The study results show risk propensity plays a significantly moderate role in relations of attitude, subjective norms, and financial expectation to intentions with the analysis indicating a positive effect. Its results will be able to provide more reference for the SRI studies and a new angle for capital market researchers, market information providers, and investors.